The Contribution of Professor Esen Bekturov to Physical Chemistry of Polymers - Kudaibergenov, S.E. (KU Publ., 2022)
The article is dedicated to the 90th anniversary of Academician Esen Abikenovich Bekturov, a prominent Kazakhstani chemist who has made an outstanding world contribution to the physical chemistry of polymers. His scientific interests focused on the study of water-soluble and water-swelling polymers, interpolymer and polymer-metal complexes, polymeric catalysts and associates, polymeric hydrogels, molecular complexes of polymers, nanomaterials and nanotechnology are summarized in numerous monographs published in Japan, Germany, Poland, and Kazakhstan. The essay briefly reflects the life path, creativity, scientific and pedagogical activity of Professor Esen Bekturov, as well as the most important and prominent publications. His role in the transfer of knowledge, training of high-qualified specialists, his contribution to Research and Development (R&D), recognized by numerous International and Republican awards and participation at International Conferences and Symposiums, are highlighted.
Профессор Есен Бектұровтың полимерлердің физикалық химиясына қосқан үлесі
Вклад профессора Есена Бектурова в физическую химию полимеров
Keywords: Physical Chemistry; Polymers; Professor Esen Bekturov; Contribution